Processes of communication and dissemination of science: the challenges of science policy guidelines in Colombia - Niño-Sandoval, Yaddy (2023)
“Introduction: The present study aims to identify the characteristics of public policy relating to the Social Appropriation of Knowledge (SAK) in Colombia, generated between 2020 and 2021, on the communication and dissemination of science. Furthermore, the study aims to determine what incentives are offered by these policies to promote the communication and dissemination of science, and what importance is given to the use of digital scenarios. Method: This is done through a comparative analysis of Colombia’s guidelines of public science policies using a bibliographical review. Results and discussion: With this analysis, it is concluded that the policies resulting from 22 years of reflection in Colombia aim to strengthen the SAK in the communication of science, understood in specific relation to dissemination, which is understood as activities that make scientific knowledge accessible to a much wider audience. Conclusion: The digital scenarios are proposed as communicative spaces to spread knowledge to communities and strengthen the science-society relationship.“